Enhancing Singlet Oxygen Generation in Conjugates of Silicon Nanocrystals and Organic Photosensitizers - Beri, Deski; Jakoby, Marius; Busko, Dmitry; Richards, Bryce S.; Turshatov, Andrey (Frontiers in Chemistry, 2020)
Silicon nanocrystals (SiNCs) are regarded as a green and environmentally friendly material when compared with other semiconductor nanocrystals. Ultra-small SiNCs (with the size 4.6-5.2 nm) demonstrate strong UV absorption and photoluminescence in the near infrared (NIR) range with the high photoluminescence quantum yield (PLQY) up to 60%. In contrast to nonporous silicon, ultra- small SiNCs does not possess an intrinsic ability to generate singlet oxygen (1O2). However, we demonstrated that SiNC-dye conjugates synthesized via microwave assistant hydrosilylation reaction produce 1O2 with moderate quantum yield () up to 27 % in cyclohexane. These interesting results were obtained via measurements of singlet oxygen phosphorescence at 1260 nm. SiNCs play an important role in the production of singlet oxygen as SiNCs harvest UV and blue radiation and transfer absorbed energy to a triplet state of the attached dyes. It increases the population of the triplet states and leads to the enhancement of the singlet oxygen generation. Simultaneously, the SiNC-dye conjugates demonstrate NIR luminescence with the PLQY up to 22 %. Thus, the luminescence behavior and photosensitizing properties of the SiNC-dye conjugates can attract interest as a new multifunctional platform in the field of bio-applications.